2011
DOI: 10.1097/wco.0b013e328341e2b2
|View full text |Cite
|
Sign up to set email alerts
|

Ocular torsion and vertical misalignment

Abstract: The effects of head position and of lesions of the nodulus are assuming increasing importance in analysis and differential diagnosis of vertical misalignment and torsion of the eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…In contrast, when the dentate nucleus was spared and lesions were located in the middle cerebellar peduncle, tonsil, biventer, and inferior semilunar lobules, OTR was observed ipsilaterally (14,15). Moreover, unilateral involvement of the nodulus may be a cause of OTR (16)(17)(18)(19)(20). There have been only three reported cases of isolated bilateral nodular infarction (19,20).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, when the dentate nucleus was spared and lesions were located in the middle cerebellar peduncle, tonsil, biventer, and inferior semilunar lobules, OTR was observed ipsilaterally (14,15). Moreover, unilateral involvement of the nodulus may be a cause of OTR (16)(17)(18)(19)(20). There have been only three reported cases of isolated bilateral nodular infarction (19,20).…”
Section: Discussionmentioning
confidence: 97%
“…The utricular signals are relayed from the vestibular nuclei, medullary reticular formation, inferior olive, and lateral reticular nucleus to the nodulus and uvula in the cerebellum, and influence the deep cerebellar nucleus (12). Consequently, OTR can be induced by involvement of the cerebellum, although the precise region responsible still remains controversial (13)(14)(15)(16)(17)(18)(19)(20). Lee et al (13) reported two cases of OTR secondary to unilateral infarction of the anterior inferior cerebellar artery, and indicated that damage to the inner ear of the root entry zone of the cranial eighth nerve might be responsible for OTR.…”
Section: Discussionmentioning
confidence: 99%
“…These vestibular system abnormalities can be demonstrated using various vestibular function tests. Fundus photography is used to evaluate the ocular torsion (OT) resulting from the static imbalance of the roll plane sensed by the otolith receptors in the utricles [1]. The OT abnormality in acute unilateral vestibular loss usually resolves within days or weeks [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Incluso en reposo, el sistema vestibular está expuesto a la aceleración lineal constante ejercida por la fuerza de gravedad. Este estímulo genera una representación interna, subjetiva de verticalidad, en la cual se basan las respuestas cervicales, espinales y musculoesqueléticas en general para mantener el cuerpo en una posición deseada con respecto al suelo, por ejemplo, erecto al caminar [15][16][17] .…”
Section: Introductionunclassified